2019
DOI: 10.1002/cbin.11126
|View full text |Cite
|
Sign up to set email alerts
|

Bone mesenchymal stem cell‐conditioned medium attenuates the effect of oxidative stress injury on NSCs by inhibiting the Notch1 signaling pathway

Abstract: Numerous studies have demonstrated the therapeutic effect of bone mesenchymal stem cells on spinal cord injury (SCI), especially on neural stem cells (NSCs). However, the predominant mechanisms of bone mesenchymal stem cells (BMSCs) are unclear. Recently, some researchers have found that paracrine signaling plays a key role in the therapeutic capacity of BMSCs and emphasized that the protective effect of BMSCs may be due to paracrine factors. In this study, we aimed to investigate the potential mechanisms of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Our results showed that treatment of hBMSC exposed to H 2 O 2 with different concentrations of MSC-CM restored the effect of H 2 O 2 and increased the viability of these cells. This is comparable to results from previous studies showing a concentration dependent effect of MSC-CM in restoring the adverse effects of H 2 O 2 on neural stem cells [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed that treatment of hBMSC exposed to H 2 O 2 with different concentrations of MSC-CM restored the effect of H 2 O 2 and increased the viability of these cells. This is comparable to results from previous studies showing a concentration dependent effect of MSC-CM in restoring the adverse effects of H 2 O 2 on neural stem cells [27].…”
Section: Discussionsupporting
confidence: 90%
“…Studying the inter-individual variations in MSC-CM between donors as well as determining the number of donors to use for controlling such variations is important and needs further investigation. It has been reported that, under oxidative conditions, the use of MSC-CM increases cell viability and activity of antioxidant enzymes, while reducing ROS and apoptosis [27,29]. Likewise, the present study detected higher production of the antioxidant enzyme-SOD with decreased ROS generation in hBMSC exposed to H 2 O 2 after treatment with MSC-CM.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, it is difficult to interpret whether enhanced SOD activity and/or SOD expression is due to MSCs or host‐tissue‐derived SOD. In in vitro studies, MSC‐CM or MSCs in transwell cocultures promote SOD activity in tert‐Butyl hydroperoxide or UV‐exposed fibroblasts, H 2 O 2 ‐treated neural stem cells or retinal ganglion cells, and dexamethasone‐induced muscle atrophy model 60,73‐76 . These studies suggest that MSCs enhance SOD activity in cells exposed to oxidative stimuli.…”
Section: Antioxidative Mechanisms Of Mscsmentioning
confidence: 78%
“…Currently, there are few studies about the mechanism of BMSCs regulating oxidative stress to improve POF ovarian function, but they have been widely studied in other diseases. Niu Y et al revealed that BMSCs-CM could alleviate oxidative stress injury of neural stem cells through decreasing the expression of lactate dehydrogenase and malondialdehyde, increasing the expression of SOD and inhibiting the Notch1 signaling pathway (143). Moreover, BMSCs help to reduce oxidative stress and inflammation via down-regulating NF-kB signaling pathway, thereby reducing doxorubicin-induced nephropathy (144).…”
Section: Antioxidationmentioning
confidence: 99%